Pengelolaan Pembelajaran Akuntansi Di Smk Negeri 1 Sragen - UTAMI, Lilis Retno (2016)
Aim of the research are to describes planning, organizing, actuating and evaluating of Accounting Learning At State Vocational High School 2 Of Sragen. The type of this research is qualitative research with etnography design. Data was collected by interview, observation and documentation. Data analysis technique using an interactive model of analysis, whereas the validity of the data examined by source triangulation method. Results of this study concluded that: 1) preparation of planning Accounting learning at State Vocational High School begin with learn the content standards and competency standards. In addition, also need to study the syllabus for the adjustment education calendar; preparing lesson plans. In lesson plans consists of the identity of the school, subject, class / semesters, CS (Competency Standards), BC (basic competence), meetings and time allocation, indicators, learning objectives, teaching materials, teaching methods, learning steps, tools / materials / learning resources, assessment, 2) Organizing of Accounting learning at State Vocational High School, covering the organization of the subject matter in sequence according to the reference syllabus, organizing academic calendar for the implementation of hands-on lessons, organizing classes in order to avoid noise with supervision and sanctions, organizing difficulties of the subject matter and find a settlement; 3) In the process of Accounting learning in vocational high school beginning with teacher is delivering salutation, followed by observing or observation of hygiene class. Teacher doing absent students. Check homework assignments, and to motivate the students by explaining the usefulness of the material accounting lessons to be utilized in everyday life, 4) In evaluation of accounting learning at vocational high school, teachers' activities are distributed about the tests to the students. Students can answer the student handbook. Test measurement evaluation of learning used can demonstrate the ability to create financial reports. Teachers can take action evaluation results to students whose value under MCC (Minimum Completeness Criteria) with remedial, otherwise if there are questions that are considered difficult for students, then students are given enrichment. Evaluation of Accounting Learning at Vocational High School have special evaluation models, namely sheets of scientific performance.